2010
DOI: 10.1002/humu.21209
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effect of sequence variation on regulatory interactions

Abstract: ABSTRACT:The increasing amount of sequence data provides new opportunities and challenges to derive mechanistic models that can link sequence variations to phenotypic diversity. Here we introduce a new computational framework to suggest possible consequences of sequence variations on regulatory networks. Our method, called sTRAP (strap.molgen.mpg.de), analyses variations in the DNA sequence and predicts quantitative changes to the binding strength of any transcription factor for which there is a binding model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
89
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 37 publications
0
89
0
Order By: Relevance
“…strong sequence variants in cis-regulated H3K4me3 regions affect the affinity of a TF by altering the sequence of its binding site (Manke et al 2010). For each motif of the TRANSFAC database (Wingender et al 1996; http://www.gene-regulation.com), we tested whether high scores for differential TF binding occurred more often in cis-regulated regions compared with the remaining regions.…”
Section: Genetic Determinants Of Histone Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…strong sequence variants in cis-regulated H3K4me3 regions affect the affinity of a TF by altering the sequence of its binding site (Manke et al 2010). For each motif of the TRANSFAC database (Wingender et al 1996; http://www.gene-regulation.com), we tested whether high scores for differential TF binding occurred more often in cis-regulated regions compared with the remaining regions.…”
Section: Genetic Determinants Of Histone Modificationsmentioning
confidence: 99%
“…For each PWM from the TRANSFAC database set (Wingender et al 1996; http://www.generegulation.com) of nonredundant PWMs, we scored the difference of binding affinities of the reference and alternative alleles using the sTRAP method (Manke et al 2010). We then classified the SNPs into two classes: SNPs in cis-regulated regions (FDR < 0.1) and SNPs in other regions.…”
Section: Differential Transcription Factor Bindingmentioning
confidence: 99%
“…Recent projects such as the 1000 Genomes Project (1kGP) (Abecasis et al, 2012) attempt to systematically map genome-wide variants, while the ENCODE Project database's (Bernstein et al, 2012) main aim is to find DNA functional elements in the human genome. These have spurred a scientific trend for creating algorithms that select rSNPs and quantify their functional impact (Lower et al, 2013, Chen et al, 2014, Bryzgalov et al, 2013, Li et al, 2013, Macintyre et al, 2010, Manke et al, 2010, Teng et al, 2012, Ward & Kellis 2012, Holm et al, 2010. There are several rSNP databases (Guo et al, 2014, Ning et al, 2014 which could have an application in diagnostics and personalized medicine.…”
mentioning
confidence: 99%
“…There are many pitfalls and limitations from the existing algorithms and databases for achieving an accurate prediction of the transcription regulation: (1) the disease-associated SNPs in GWAS datasets (Bryzgalov et al, 2013, Li et al, 2013, Teng et al, 2012, Ward & Kellis 2012 may not be in fact causal, since its selection is due to the linkage to other causal SNPs (Levo & Segal 2014); (2) chromatin accessibility datasets lack many specific cell lines (Bryzgalov et al, 2013, Macintyre et al, 2010, Manke et al, 2010, Teng et al, 2012 or are limited in their use , Li et al, 2013, Ward & Kellis 2012; (3) there are few resources integrating genetic variant databases and expression profile information (Yang et al 2010, Holm, Melum, Franke, & Karlsen, 2010, though there is a recent effort in providing tissue-specific gene expression and genotype information (GTEx Consortium, 2015); and (4) the absence of the quantification of the impact of multiple TFBSs of the same TF in the regulatory region (also called homotypic redundancy) , Bryzgalov et al, 2013, Macintyre et al, 2010, Teng et al, 2012, Ward & Kellis 2012, which is an important feature in the regulation of gene expression (Gotea et al, 2010, Spivakov et al, 2012. This is because it has been suggested that the more TFBSs for a single TF in the same region, the less impact a single TFBS perturbation will have (Sharon et al 2012, Smith et al 2013.…”
mentioning
confidence: 99%
“…To investigate potential regulatory SNPs, we used sTRAP [27] , which calculates the difference in binding affinity between common and rare allele-containing sequences. Sequences overlapping a differentially methylated CpG site (5 bp before and after) were used as input sequence.…”
Section: Transcription Regulation Analysismentioning
confidence: 99%